Depósitos lacustres rasos da Formação Pedra de Fogo, Permiano da bacia do Parnaíba, Brasil - ARAÚJO, Raphael Neto (Universidade Federal do Pará, 2019)
The Permian Pedra de Fogo Formation, exposed in the east and west borders of Parnaíba Basin, northern Brazil, represent one of the most important terminal Paleozoic sedimentary record of the Western Gondwana. The main lithotypes of this unit are sandstones, shales, carbonate rocks, evaporites. The unit is famous for its large amounts of chert and presence of well-preserved Permian flora. In the last decades of the 20 th century, previous works interpreted the paleoenvironment of the Pedra de Fogo Formation as transitional fluvial-deltaic deposits, storm influenced-shallow neritic (marine) to coastal sabkha plain, lacustrine and fluvial deposits with contribution of marine-aeolian sediments and shallow to restrict sea or epicontinental type. Facies analysis focused principally on outcrops of the base and upper part of this unit, involving approximately 100 m thick of the siliciclastic succession. Eleven sedimentary facies were recognized and grouped into three facies associations (FA), representative of a shallow lacustrine depositional system associated with mudflat and ephemeral rivers. FA1 is interpreted as mudflat deposits, consisting of laminated claystone/siltstone, sandstones/pelites with mud cracks and sandstones with cross-lamination, massive and megaripple beddings. Silicified nodules and molds like popcorn indicate evaporites deposits. Other common features are silica concretions, silicified teppes and silcretes. FA2 represents deposits of nearshore and consists of fine-grained sandstones with even parallel lamination, climbing ripple cross-lamination, massive and megaripple beddings, as well as, laminated mudstone/siltstone. FA3 refers to wadi/inundite deposits, generally organized in fining upward meter-scale cycles, consisting of conglomerates and medium-grained pebbly sandstones with massive bedding and cross-stratification, and claystone/siltstone with even parallel to wavy lamination. Tabular beds are frequent in FA3 while scour-and-fill geometry is rare. The alternation of pelites and fine to medium-grained sandstones with even parallel to wavy lamination are the main framework of the Pedra de Fogo Formation. Bioturbations, shrinkage cracks and different types of siliceous concretions, as well as, teeth of fish, ostracods, bryozoans and scolecodontes are common in the studied succession. Silicified plant remains, preliminarily classified to the genus Psaronius, are found in situ, concentrated near the upper contact with Motuca Formation, considered here as excellent biostratigraphic markers for the upper Pedra de Fogo Formation. Mudflats deposits occur in the basal Pedra de Fogo succession suggesting arid and hot climates for the early Permian. The midlle Permian was predominated semiarid allowing the proliferation of fauna and flora in humid regions adjacent and into the lake margin. The ephemeral fluvial inflow or wadis carried plant remains and terrigenous to the lake generating inundites. Retreat and expansion phases characterized the Pedra de Fogo lake, induced by extreme climatic changes influencing not only the sedimentation pattern as also the fossilization of the best well-preserved Permian fauna and flora. In the late Permian, the climate again became hot and arid due to the complete aggregation of Pangea supercontinent, favoring the deposition of Motuca red beds and establishment of Sambaíba erg, near in the Permian-Triassic boundary.